MATHEMATICS IN MOROCCAN UNIVERSITIES - Zineb El Jaoussi; Al Achhab Sakina; Aziz Arbai; Mohammed Khaldi (European Scientific Journal, ESJ, 2013)
This works deals with the teaching and learning of mathematics in Moroccan universities. Our Goal is to better understand difficulties encountered by students, with math, and to study in which measure the integration of new technologies of information and communication may help them overcome these difficulties, by favoring interactions between representation by ICT and classical representation of the concerned course. On the basis of the instrumental approach of computers in teaching, we start from the hypothesis that succeeding to this type of mathematical tasks requires, beyond knowing adequate commands and their syntax, learning specific instrumented techniques, in a context taken in charge by the institution. In our thesis, a technique to represent called 3D technology occupies a central part, as a means to reduce the distance between the knowledge teachable and the knowledge to be taught. The works includes an institutional analysis (ecological analysis of university curriculum) about the teaching of mathematics and the use of 3D technology, as well as two experiments, without and with the other.